James Gillespie Blaine family papers - Blaine, James Gillespie, 1830-1893.
Family and general correspondence, speeches and writings, diaries, memoirs, notebooks, scrapbooks, and other papers documenting Blaine's public career. Includes a draft of his book, "Twenty Years of Congress" (1884-1886). Documents national and Republican Party politics during Reconstruction and afterward, the presidential campaign of 1884, and foreign policy in regard to Europe and Latin America. Portions of the general correspondence and the financial papers relate to Blaine's extensive business activities. The family correspondence series deals mainly with personal and family matters, but political and diplomatic affairs are discussed throughout.
Family correspondents include Blaine's wife, Harriet S. Blaine; his son, Walker Blaine; his daughter, Margaret Blaine Damrosch; his father, Ephraim Lyon Blaine; his mother, Maria Louise Gillespie Blaine; his great-grandfather, Ephraim Blaine; and his secretary, Thomas H. Sherman. The autograph collection contains single letters of Benjamin Franklin, Henry Wadsworth Longfellow, Benjamin Vaughan, and Daniel Webster, two letters of W. E. Gladstone, a copy of a George Washington letter, an endorsement of Abraham Lincoln, holograph notes of Henry Clay and of James Madison, and an autograph of John Quincy Adams.
Correspondents include William B. Allison, Chester Alan Arthur, George S. Boutwell, Benjamin Helm Bristow, Edwin C. Burleigh, Benjamin F. Butler, J. D. Cameron, Simon Cameron, Andrew Carnegie, William E. Chandler, Zachariah Chandler, George William Childs, Schuyler Colfax, Alonzo B. Cornell, Samuel Sullivan Cox, Stephen B. Elkins, William Maxwell Evarts, Thomas Ewing, Cyrus W. Field, Hamilton Fish, Charles R. Flint, Patrick Ford, Charles Foster, James A. Garfield, Lucretia Rudolph Garfield, George Congdon Gorham, Ulysses S. Grant, Horace Greeley, Galusha A. Grow, Eugene Hale, Murat Halstead, Hannibal Hamlin, John M. Harlan, Benjamin Harrison, Bret Harte, John Hay, Rutherford Birchard Hayes, Phineas Warrener Hitchcock, E. R. Hoar, George Frisbie Hoar, O. O. Howard, Timothy O. Howe, Henry M. Hoyt, William H. Hunt, Robert G. Ingersoll, Robert Todd Lincoln, Henry Cabot Lodge, John Alexander Logan, Alexander K. McClure, William McKinley, Edward McPherson, Joseph Medill, Warner Miller, Edwin D. Morgan, Justin S. Morrill, Lot M. Morrill, Baron Julian Pauncefote, William Walter Phelps, Wendell Phillips, Thomas B. Reed, Whitelaw Reid, Horace Rublee, Robert C. Schenck, Ellen Ewing Sherman, John Sherman, Rachel Sherman, William T. Sherman, Charles E. Smith, William Henry Trescott, Israel Washburn, E. B. Washburne, Thurlow Weed, William Windom, and Fernando Wood.
Microfilm edition available in part
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Serial and Government Publications Division.
U.S. secretary of state, U.S. representative and senator from Maine, and journalist.
Collection material in English.
Keywords: Adams, John Quincy, -- 1767-1848.; Allison, William B. -- 1829-1908 -- Correspondence; Arthur, Chester Alan, -- 1829-1886 -- Correspondence; Blaine family; Blaine, James G., -- Mrs., -- 1828-1903 -- Correspondence; Blaine, Ephraim Lyon, -- 1796-1850 -- Correspondence; Blaine, Ephraim, -- 1741-1804 -- Correspondence; Blaine, Maria Louise Gillespie -- Correspondence; Blaine, Walker, -- d. 1890 -- Correspondence; Boutwell, George S. -- 1818-1905 -- Correspondence; Bristow, Benjamin Helm, -- 1832-1896 -- Correspondence; Burleigh, Edwin C. -- 1843-1916 -- Correspondence; Butler, Benjamin F. -- 1818-1893 -- Correspondence; Cameron, J. D. -- 1833-1918 -- Correspondence; Cameron, Simon, -- 1799-1889 -- Correspondence; Carnegie, Andrew, -- 1835-1919 -- Correspondence; Chandler, William E. -- 1835-1917 -- Correspondence; Chandler, Zachariah, -- 1813-1879 -- Correspondence; Childs, George William, -- 1829-1894 -- Correspondence; Clay, Henry, -- 1777-1852.; Colfax, Schuyler, -- 1823-1885 -- Correspondence; Cornell, Alonzo B., -- 1832-1904 -- Correspondence; Cox, Samuel Sullivan, -- 1824-1889 -- Correspondence; Damrosch, Margaret Blaine, -- 1867-1949 -- Correspondence; Elkins, Stephen B. -- 1841-1911 -- Correspondence; Evarts, William Maxwell, -- 1818-1901 -- Correspondence; Ewing, Thomas, -- 1829-1896 -- Correspondence; Field, Cyrus W. -- 1819-1892 -- Correspondence; Fish, Hamilton, -- 1808-1893 -- Correspondence; Flint, Charles R. -- 1850-1934 -- Correspondence; Ford, Patrick, -- 1835-1913 -- Correspondence; Foster, Charles, -- 1828-1904 -- Correspondence; Franklin, Benjamin, -- 1706-1790 -- Correspondence; Garfield, James A. -- 1831-1881 -- Correspondence; Garfield, Lucretia Rudolph, -- 1832-1918 -- Correspondence; Gladstone, W. E. -- 1809-1898 -- Correspondence; Gorham, George C. -- 1832-1909 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Greeley, Horace, -- 1811-1872 -- Correspondence; Grow, Galusha A. -- 1823-1907 -- Correspondence; Hale, Eugene, -- 1836-1918 -- Correspondence; Halstead, Murat, -- 1829-1908 -- Correspondence; Hamlin, Hannibal, -- 1809-1891 -- Correspondence; Harlan, John Marshall, -- 1833-1911 -- Correspondence; Harrison, Benjamin, -- 1833-1901 -- Correspondence; Harte, Bret, -- 1836-1902 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Hayes, Rutherford Birchard, -- 1822-1893 -- Correspondence; Hitchcock, Phineas Warrener, -- 1831-1881 -- Correspondence; Hoar, E. R. -- 1816-1895 -- Correspondence; Hoar, George Frisbie, -- 1826-1904 -- Correspondence; Howard, O. O. -- 1830-1909 -- Correspondence; Howe, Timothy O. -- 1816-1883 -- Correspondence; Hoyt, Henry M. -- 1830-1892 -- Correspondence; Hunt, William H. -- 1823-1883 -- Correspondence; Ingersoll, Robert Green, -- 1833-1899 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Lincoln, Robert Todd, -- 1843-1926 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Logan, John Alexander, -- 1826-1886 -- Correspondence